Syngas Production via Methane Dry Reforming: A Novel Application of SmCoO3 Perovskite Catalyst - Osazuwa, Osarieme U.; Setiabudi, Herma Dina; Ruwaida, Abdul Rasid; Cheng, Chin Kui (Elsevier Ltd, 2017)
In this study, SmCoO3 perovskite catalyst have been synthesized by the sol-gel citrate method and for the first time, applied as catalyst for the production of syngas (H2 and CO) via methane dry reforming reaction. The perovskite catalyst was characterized (pre- and post-reaction) to determine its physicochemical properties. Characterization of the calcined perovskite catalyst showed the formation of perovskite structure only. No other crystalline phases were detected. Prior to the catalytic test, the effects of reducing SmCoO3 perovskite catalyst with H2 (for activation) in the methane dry reforming reaction were investigated. Results showed no significant effects of H2 reduction on the activity of the SmCoO3 perovskite catalyst. This suggests that there was an in-situ reduction of SmCoO3 which was confirmed by XRD analysis of spent catalyst. Subsequently, reactant gases (CO2 and CH4) with partial pressure ranged 6.8-60.8 kPa and reaction temperature ranged 973-1073 K were employed for the reaction study. Results from the catalytic activity yielded maximum conversion of 93% for both reactants, at reactants partial pressure of 20.3 kPa (stoichiometric point). In addition, syngas with maximum percentage yield of 67% and 65% for H2 and CO, respectively, was produced from the methane dry reforming reaction. Used catalyst characterization showed the existence of carbon deposit which could have emanated from methane decomposition.